1998
DOI: 10.1164/ajrccm.158.4.9707143
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Exhaled Nitric Oxide and Childhood Asthma

Abstract: The purpose of the study was to determine if exhaled nitric oxide levels in children varied according to their asthmatic and atopic status. Exhaled nitric oxide was measured in a sample of 93 children attending the North West Lung Centre, Manchester, United Kingdom, for the clinical evaluation of a respiratory questionnaire being developed as a screening tool in general practice. The clinical assessment included full lung function, skin prick testing, and exercise challenge. Children were said to be asthmatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
83
2
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 13 publications
19
83
2
4
Order By: Relevance
“…In addition, our results suggest that the eNO level of atopic asthmatic children is greater than that of non-atopic asthmatic children. These findings are consistent with previous studies, in which eNO levels from two to four times higher than normal were found in atopic asthmatic children [7], teenagers [15] and adults [16]. Among non-asthmatic children, atopic subjects had higher eNO concentrations than non-atopic subjects, which contrasts with previous results showing no difference in eNO levels between atopic and nonatopic individuals either in children [7] or in adults [15,16].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our results suggest that the eNO level of atopic asthmatic children is greater than that of non-atopic asthmatic children. These findings are consistent with previous studies, in which eNO levels from two to four times higher than normal were found in atopic asthmatic children [7], teenagers [15] and adults [16]. Among non-asthmatic children, atopic subjects had higher eNO concentrations than non-atopic subjects, which contrasts with previous results showing no difference in eNO levels between atopic and nonatopic individuals either in children [7] or in adults [15,16].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the association of asthma and atopy appears to be the most consistent predictor of increased eNO level. A similar result was obtained by Frank et al, 5 who found that the eNO geometric mean was significantly higher in children with atopic asthma than in nonatopic asthmatic children. These findings further support the hypothesis that in children atopy is a major determinant of increased eNO levels, mainly when associated with clinical manifestation of asthma.…”
Section: Discussionsupporting
confidence: 88%
“…[2][3][4] However, other studies did not find a relation between atopy and eNO levels in children. 1,5,15 In particular, Latzin et al 15 failed to demonstrate a relation between atopy and eNO levels in 4-to 18-year-old healthy children. A possible explanation for these conflicting results might be found in the dimension of the studied sample, 5 the different prevalence of atopic children in the study samples, and the different age distributions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations